Lepus othus Merriam 1900 - Robert S. Hoffmann (Smithsonian Institution Press, 1993)
Lepus othus Merriam, 1900. Proc. Washington Acad. Sci., 2:28. TYPE LOCALITY: "St. Michaels, [Norton Sound], Alaska." [USA]. DISTRIBUTION: W and SW Alaska (USA); formerly perhaps northwestward to Pt. Barrow; as here interpreted, also E Chukotsk (Russia). STATUS: Rare, perhaps decreasing in range and numbers (Flux and Angermann, 1990). SYNONYMS: poadromus Merriam, 1900; tschuktschorum Nordquist, 1883. COMMENTS: Formerly included in arcticus or timidus (see comments therein). Regarded as distinct by Hall (1981) and by Flux and Angermann (1990), who, however, followed A. J. Baker et al. (1983) in allying populations from E Chukotsk (Russia) with Alaskan populations; but see also Pavlinov and Rossolimo (1987). Angermann (in litt., 1992) considered othus as "probably conspecific" with timidus. Published as part of Robert S. Hoffmann, 1993, Order Lagomorpha, pp. 807-827 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 819, DOI: 10.5281/zenodo.7353088